Recent Developments in Polyene Cyclizations and Their Applications in Natural Product Synthesis - Barrett, Anthony G. M.; Ma, Tsz-Kan; Mies, Thomas (Synthesis, 2019)
Cascade polyene cyclization reactions are highly efficient and elegant bioinspired transformations that involve simultaneous multiple bond constructions to rapidly generate complex polycyclic molecules. This review summarizes the most prominent work on a variety of cationic and radical cascade cyclizations and their applications in natural product synthesis published between 2014 and 2018.1 Introduction2 Cationic Polyene Cyclizations2.1 Lewis Acid Mediated Polyene Cyclizations2.2 Brønsted Acid Mediated Polyene Cyclizations2.3 Halogen Electrophile Initiated Polyene Cyclizations2.4 Sulfur Electrophile Initiated Polyene Cyclizations2.5 Transition-Metal-Mediated Cationic Polyene Cyclizations3 Radical Polyene Cyclizations3.1 Transition-Metal-Mediated Radical Polyene Cyclizations3.2 Photocatalyst-Mediated Polyene Cyclizations4 Origin of Stereocontrol in Polyene Cyclizations5 Conclusion
Keywords: polyene cyclization; cascade reaction; carbon–carbon bond formation; natural products; total synthesis